Development Strategy of Community-Based Tourism in Taro Tourism Village, Gianyar, Bali - Yanti, Deva; Sara, I Made; Laksmi, Putu Ayu Sita (Journal of Tourism Economics and Policy, 2026)
Community-Based Tourism (CBT) is a strategic approach to sustainable tourism development that places local communities as the main actors and beneficiaries. This study aims to analyze the internal and external factors influencing the development of CBT in Taro Village and to examine the role of the community in the planning, implementation, monitoring, and utilization of tourism development outcomes. This research applies a qualitative method with a descriptive design. Data were collected through observation, in-depth interviews with key informants, and documentation review. The data were analyzed using a SWOT framework to identify strengths, weaknesses, opportunities, and threats affecting CBT development. The findings show that internal strengths include abundant natural, cultural, and spiritual resources, strong social capital, and active community participation. However, internal weaknesses remain, such as limited human resource capacity, suboptimal tourism management, and inadequate infrastructure. Externally, opportunities are driven by increasing tourist interest in cultural and sustainable tourism and supportive government policies, while threats include destination competition, changing tourism trends, and potential environmental degradation. The study concludes that CBT development in Taro Village has strong potential for sustainable growth, provided that capacity building, institutional strengthening, and stakeholder collaboration are enhanced.